Sent to Heal! About the Biblical Roots, the History, and the Legacy of Medical Missions - Christoffer H. Grundmann (Health for All Nations, 2014)
The article situates medical missions within the broader context of the healing ministry of the Christian Church. In its first part it sketches the biblical tradition of this healing ministry and its meaning in the life of Jesus and his disciples. The second section provides a survey of Christian healing initiatives and care for the sick from the Early Church until the emergence of medical missions in the nineteenth century. The third part focuses on the development of the concept medical missions and its changes up to the present, while the final part briefly reflects on the lasting legacy of medical missions which is seen in that, if Christians ignore and neglect corporeality, they disgrace God the Creator and God's incarnation in Jesus Christ. The article therefore concludes that medical missions remind the Church that at the root of too spiritual a concept of mission and too materialistic a concept of health lies a misconceived, non-biblical anthropology which profoundly distorts the Christian witness to God incarnate in Christ.